Implementasi Metode Bercerita Dalam Menanamkan Nilai-Nilai Agama Dan Moral Pada Anak Usia Dini Di Ra Al-Furqon Madina : Implementation of the Storytelling Method in Instilling Religious and Moral Values in Early Childhood at Ra Al-Furqon Madina - Wahyuningsih, Riris; Ulya, Naimatul (Prodi Pendidikan Islam Anak Usia Dini Sekolah Tinggi Agama Islam Negeri Mandailing Natal- Sumatera Utara, 2024)
Implementation of the Storytelling Method in Instilling Religious and Moral Values ​​in Early Childhood at RA Al-Furqon Madin). The process of instilling religious and moral values ​​in early childhood must look at the child's development stages. Instilling religion and morals in children can be realized by participating in school activities, children will get real experience provided by teachers. One method used by teachers to instill religion and morals in children is through story activities. It is hoped that the need to instill religion and morals in the story method will enable the values ​​taught to be internalized and interpreted by children without pressure. This thesis reviews the implementation of the storytelling method in instilling religious and moral values ​​at Raudhatul Athfal (RA) Al-Furqon Madina, with the aim of describing the implementation of the storytelling method in instilling religious values ​​in early childhood at RA Al-Furqon, to describe the instillation religious and moral values ​​at RA Al-Furqon, to explain the supporting and inhibiting factors for instilling religious and moral values ​​from the implementation of the storytelling method at RA Al-Furqon. This research is included in qualitative descriptive research. Data collection was carried out using observation, interviews and documentation methods. Data analysis was carried out after the data was collected using triangulation techniques (comparing, checking, checking the validity of the data) with the results of observations, interviews and the results of observations in the documentation. The results of the implementation of the storytelling method applied at RA Al-Furqon are siroh stories and this method really helps young children to instill religious and moral values ​​at RA Al-Furqon. The teacher applies the storytelling method in accordance with appropriate and good techniques so that The values ​​contained in each story can be reflected in children's habits and behavior in their daily lives.